1981
DOI: 10.1007/bf02887323
|View full text |Cite
|
Sign up to set email alerts
|

Studies of chemical methods for assessing oxidative quality and storage stability of feeding oils

Abstract: Peroxide value (PV), thiobarbimdc acid number (TBA), anisidine value (AV), percent free fatty acids (FFA), and carbonyl value (CV) methods were compared in different experiments for their sensitivity and practicality in assessing the oxidative quality of four feeding oils: salmon oil, soybean oil, canola oil (oil from low emcic acid, low gtucosinolate rapeseed), and canola soap stocks. In the first experiment, among the four methods (PV, AV, TBA and FFA) studied, PV appeared to be the most practical for its se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Similar results were reported by Eidhin and O'Beirne [59] for sunflower oil stored at 4 °C or room temperature and by Lee et al [55] for soybean, sunflower and olive oils stored at 25 °C or 40 °C. The same pAV vs. time pattern was revealed by Hung and Slinger [61] when storing different oils (salmon, canola and soybean) at room temperature. Other investigators have found that the total amount of carbonyls present in an oil changes in an erratic manner, or decreases, during refrigeration and frozen storage of food [62].…”
Section: Sunflower Tahini and Oil P-anisidine Values During Storagesupporting
confidence: 59%
“…Similar results were reported by Eidhin and O'Beirne [59] for sunflower oil stored at 4 °C or room temperature and by Lee et al [55] for soybean, sunflower and olive oils stored at 25 °C or 40 °C. The same pAV vs. time pattern was revealed by Hung and Slinger [61] when storing different oils (salmon, canola and soybean) at room temperature. Other investigators have found that the total amount of carbonyls present in an oil changes in an erratic manner, or decreases, during refrigeration and frozen storage of food [62].…”
Section: Sunflower Tahini and Oil P-anisidine Values During Storagesupporting
confidence: 59%
“…The production of each of these compounds has different lag phases. Peroxides are produced first, followed by malonaldehyde and finally by aldehydes (Hung & Slinger 1981;Frankel 1991), although many other products (ketones, alcohols, alkanes, alkenes) are also produced. All of the test meals were found to have undetectable levels of peroxides.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is commonly acknowledge that the starting raw material is critical in producing high quality oils, little is known on how oil quality changes as a function of storage time and temperature of the raw materials. While most researchers have focus on loss of oil quality after extraction from the initial fresh raw material [18][19][20][21], few have examined the changes with storage of the starting raw material prior to the extraction of the crude oil. This study has practical implications for the fish byproduct processing industry by determining the relationship of storage time and temperature on oil quality.…”
Section: Introductionmentioning
confidence: 99%